![image](https://tex.z-dn.net/?f=arctg%5Calpha%3D%5Carccos%5Cfrac1%7B%5Csqrt%7B1%2B%5Calpha%5E2%7D%7D%5C%5Carctg%5Csqrt+x%3E%5Carccos%5Cfrac1%7B%5Csqrt%7B1%2Bx%7D%7D%5C%5C+%5Carccos%5Cfrac1%7B%5Csqrt%7B1%2Bx%7D%7D%3E%5Carccos%281-x%29%5C%5C%5Cfrac1%7B%5Csqrt%7B1%2Bx%7D%7D%3E1-x%5C%5C%5Cfrac1%7Bx%2B1%7D%3E1-2x%2Bx%5E2%5C%5C%28x%5E2-2x%2B1%29%28x%2B1%29%3C1%5C%5Cx%5E3-x%5E2-x%2B1-1%3C0%5C%5Cx%28x%5E2-x-1%29%3D0%5C%5Cx_1%3D0%5C%5Cx%5E2-x-1%3D0%5C%5CD%3D1%2B4%5Ccdot1%5Ccdot1%3D5%5C%5Cx_2%3D%5Cfrac%7B1%2B%5Csqrt5%7D2%2C%5C%3B%5C%3B%5C%3Bx_2%3D%5Cfrac%7B1-%5Csqrt5%7D2%5C%5Cx%5Cleft%28x-%5Cfrac%7B1-%5Csqrt5%7D2%5Cright%29%5Cleft%28x-%5Cfrac%7B1%2B%5Csqrt5%7D2%5Cright%29%3C0%5C%5Cx%5Cin%5Cleft%28-%5Cinfty%3B%5C%3B%5Cfrac%7B1-%5Csqrt5%7D2%5Cright%29%5Ccup%5Cleft%280%3B%5C%3B%5Cfrac%7B1%2B%5Csqrt5%7D2%5Cright%29)
\arccos\frac1{\sqrt{1+x}}\\ \arccos\frac1{\sqrt{1+x}}>\arccos(1-x)\\\frac1{\sqrt{1+x}}>1-x\\\frac1{x+1}>1-2x+x^2\\(x^2-2x+1)(x+1)<1\\x^3-x^2-x+1-1<0\\x(x^2-x-1)=0\\x_1=0\\x^2-x-1=0\\D=1+4\cdot1\cdot1=5\\x_2=\frac{1+\sqrt5}2,\;\;\;x_2=\frac{1-\sqrt5}2\\x\left(x-\frac{1-\sqrt5}2\right)\left(x-\frac{1+\sqrt5}2\right)<0\\x\in\left(-\infty;\;\frac{1-\sqrt5}2\right)\cup\left(0;\;\frac{1+\sqrt5}2\right)" alt="arctg\alpha=\arccos\frac1{\sqrt{1+\alpha^2}}\\arctg\sqrt x>\arccos\frac1{\sqrt{1+x}}\\ \arccos\frac1{\sqrt{1+x}}>\arccos(1-x)\\\frac1{\sqrt{1+x}}>1-x\\\frac1{x+1}>1-2x+x^2\\(x^2-2x+1)(x+1)<1\\x^3-x^2-x+1-1<0\\x(x^2-x-1)=0\\x_1=0\\x^2-x-1=0\\D=1+4\cdot1\cdot1=5\\x_2=\frac{1+\sqrt5}2,\;\;\;x_2=\frac{1-\sqrt5}2\\x\left(x-\frac{1-\sqrt5}2\right)\left(x-\frac{1+\sqrt5}2\right)<0\\x\in\left(-\infty;\;\frac{1-\sqrt5}2\right)\cup\left(0;\;\frac{1+\sqrt5}2\right)" align="absmiddle" class="latex-formula">